2005
DOI: 10.2166/wst.2005.0270
|View full text |Cite
|
Sign up to set email alerts
|

Dinitrogen oxide detection for nitrification failure early warning systems

Abstract: Experiments were conducted in order to establish whether N2O could be used to predict nitrification failure (through non-invasive means). Previous research had shown a strong correlation between N2O gas and NH3 in the effluent, giving rise to the possibility N2O can be used as an indicator for failure in the nitrification process. Two pilot-scale activated sludge plants were used, each with two lanes. The smaller consisted of a 601 aeration tank and a 201 clarifier; the larger pilot plant had an aeration tank … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…More recently, Burgess et al (2002a) demonstrated a strong relationship between ammonia shock loads and the concentration of N 2 O in the off-gas from the aeration tank. This suggests that the changes in N 2 O concentration in the exhaust gas from a nitrifying process may be a useful parameter for monitoring such processes (Burgess et al, 2002b;Butler et al, 2005a). As a result, a more efficient earlywarning system for the nitrification processes can be established based on N 2 O emissions as long as the off-gas N 2 O concentration can be monitored on line.…”
mentioning
confidence: 99%
“…More recently, Burgess et al (2002a) demonstrated a strong relationship between ammonia shock loads and the concentration of N 2 O in the off-gas from the aeration tank. This suggests that the changes in N 2 O concentration in the exhaust gas from a nitrifying process may be a useful parameter for monitoring such processes (Burgess et al, 2002b;Butler et al, 2005a). As a result, a more efficient earlywarning system for the nitrification processes can be established based on N 2 O emissions as long as the off-gas N 2 O concentration can be monitored on line.…”
mentioning
confidence: 99%
“…Nitrous oxide (N 2 O) emission monitoring was used by Burgess et al [22] and Butler et al [16,23] for nitrification failure early warning. The disruption of nitrification due to shocking load, toxic substance was reflected in the immediate increasing of N 2 O emission.…”
Section: Optimization Strategies For Partial Nitrificationmentioning
confidence: 99%
“…The N 2 O emission monitoring has been used for early warning and aeration control of complete nitrification process [16,17,22,23]. The integration of N 2 O emission data in partial nitrification optimization has not been investigated.…”
Section: Partial Nitrification Considering N 2 O Emissionmentioning
confidence: 99%
“…Nevertheless, human activity may intensify these emissions, for example by the discharge of wastewater containing large organic matter concentrations that decreases the dissolved oxygen (DO) levels in water, and thus favors the N-oxides production [5]. N 2 O gas is an intermediate or a sub-product of biological processes such as denitrification and nitrification, respectively [6][7][8].…”
mentioning
confidence: 99%